Performance indicators in CSR and sustainability reports in Hungary - Karcagi-Kováts, Andrea (Applied Studies in Agribusiness and Commerce, 2012)
Corporate Social Responsibility (CSR) or Corporate Sustainability reporting is a relatively new phenomenon in Hungary. As the external pressure from the civil society, public authorities and the media has so far been fairly low, this important corporate activity emerged only at the beginning of the last decade. In spite of this, several pioneering companies have started to publish information on its environmental and social performance in recent years. CSR and sustainability reports are seen increasingly as strategic documents that offer a balanced, objective, and comprehensive assessment of a firm’s non-financial performance. In 2008 and 2009, more than a third of the 100 largest companies reported on their non-financial results (most of them were GRI based reports). In 2010, sixty-one organisations published a report about their non- financial performance, and 22 of these for only the first time. The aim of this paper is to present recent attempts to use indicators in CSR and sustainability reports. On the basis of a detailed review of 70 CSR/sustainability reports published during the last 9 years in Hungary, an analysis was made on the performance indicators appearing in the reports. The motivations of indicator selection processes was analysed and the intended roles of indicator set in communication and strategy design was presented. The significance of and limits to the proposed indicators was discussed.